2021
DOI: 10.3847/1538-4357/abcd9f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multipole Moments in the Weak Field Limit of a Black Hole Plus Halo Potential

Abstract: In this paper, we consider a Newtonian system whose relativistic counterpart describes a superimposed halo with a black hole. Our aim is to determine how the quadrupole and octupole moments affect the nature of the motion of a test particle, moving in the close vicinity of the black hole. The different types of trajectories for the test particle are mainly classified as bounded, collisional, and escaping, by using modern color-coded basin diagrams. Moreover, an additional analysis is carried out for distinguis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For this space-time, Vieira et al detected the timelike geodesic orbits of test particles and found that the octopolar term could bring about chaotic motions [93]. Through further numerical analysis, they found that the quadrupolar term also gives rise to a chaotic behavior in addendum [94]. Dubeibe further investigated the effects of the quadrupole and octupole moments on the motion of a test particle using modern color-coded basin diagrams [95] and found that the final state of the test particle was highly affected.…”
Section: Introductionmentioning
confidence: 98%
“…For this space-time, Vieira et al detected the timelike geodesic orbits of test particles and found that the octopolar term could bring about chaotic motions [93]. Through further numerical analysis, they found that the quadrupolar term also gives rise to a chaotic behavior in addendum [94]. Dubeibe further investigated the effects of the quadrupole and octupole moments on the motion of a test particle using modern color-coded basin diagrams [95] and found that the final state of the test particle was highly affected.…”
Section: Introductionmentioning
confidence: 98%
“…In the last two decades, the study of the dynamics of orbits around a single BH [4][5][6] or a BH binary [7][8][9] has become very popular. With the instrumental development of the detection and measuring techniques, it is already established that most of the galaxies consist of supermassive BHs at their galactic centres [10,11].…”
Section: Introductionmentioning
confidence: 99%